PENGAWASAN PENEMPATAN PAPAN REKLAME DI KOTA PEKANBARU TAHUN 2013 – 2014 - Maulia Putri; Muchid " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Regional autonomy as a form of decentralization of government, essentially intended to meet the interests of the nation as a whole. In order to facilitate the growth and development or construction in urban areas it is necessary to use some funds from the State peneriamaan that of local tax collection. One source of state revenue is derived from local tax levies. Local tax is a local government assets used to fund the organization of local government and regional development. Advertisement tax is one potential source of revenue, so that local governments need to do optimization. Placement of billboards outdoors have a considerable influence on life in urban areas due to media advertisements are often oriented location on the main streets of urban has the advantage, among others, a strategic location, easily accessible, agglomeration activities, completeness of facilities / social facilities and economic, as well as the readiness of the infrastructure, as a result of the desire to stand out so that the information conveyed more effectively. Billboard with all the visual characteristics have a major contribution to the impression of an environment. Billboards often placed or used in urban areas. So that the local government is more concerned with taxes rather than the beauty of the city, security and environmental safety. This is contrary to the vision mission pekanbaru one of which is the beauty. The method will be applied in this research is the application of the concept of control theory. Based on the results of research and discussion that has done research on the Implementation Monitoring Placement of Billboards in Pekanbaru then there are some things that can researcher make conclusions in this paper are: 1. Supervision placement of billboards in pekanbaru seen from all indicators ranging from setting tool gauges, conducting assessments and also held a corrective action can be said is still not performing well. 2. Factors affecting Implementation Monitoring Billboard placement in Pekanbaru as seen from all indicators from the Human Resources, forms of supervision and Infrastructures has not done well this is due to inadequate resources, such as personnel monitoring and enforcement are lacking and not comparable with the number of billboards in the community pekanbaru and less cooperation with the Department of Spatial Planning and Building Pekanbaru in conducting surveillance.Keywords: Control Theory, Billboard, Pekanbaru.